Variations in Gut Microbiome Profiles Based on Different DNA Extraction Methods: A Comparative Study - Yameng Liu; Xianchun Zhong; Yibin Wang; Kanglong Wang; Cuina Li; Xinyu Liang; Suqin Lin; Ru Zhou; Cen Xie (Advanced Gut & Microbiome Research, 2024)
Objectives. To compare four DNA extraction methods for recovering bacterial DNA from mammalian faecal samples. Methods and Results. Three commercial kits from QIAamp, TIANamp, and MAGEN, together with the classic cetyltrimethylammonium bromide (CTAB) method, were evaluated for their performance in extracting bacterial DNA from the gut microbiota of five mammals, including humans (Homo sapiens), macaques (Macaca mulatta), dogs (Canis lupus familiaris), golden hamsters (Mesocricetus auratus), and mice (Mus musculus). First, we assessed the efficiency of the four methods based on DNA yield, purity, and integrity. Then, we investigated the impact of these methods on microbial composition and diversity and examined the relative abundance of dominant phyla bacteria based on 16S rRNA gene sequencing and real-time quantitative PCR. Our results showed that the CTAB method yielded relatively larger amounts of DNA, while the MAGEN kit yielded more Firmicutes DNA and reflected the true status of the microbiota more accurately. Conclusions. Of the four methods tested, the traditional CTAB method and commercial MAGEN kit accomplished the best performance in terms of DNA concentration and Firmicutes abundance across most of the tested species. As the CTAB method and MAGEN kit exhibited different advantages, we further tested and compared their DNA extraction performance on a defined microbiota comprising six strains from four dominant phyla to see which one better reflected the true status of the microbiota. In conclusion, the MAGEN kit was found to be superior to the CTAB method, as the testing results were closer to that of the defined microbiota.